CLINICAL EVALUATION OF FIXED PARTIAL DENTURE IMPRESSION - HAYAT , N; HADI , JU; ULLAH , F; FAISAL, .; FARYAL , S; SIRAJ , B (Biological and Clinical Sciences Research Journal, 2024)
Accurate impressions of teeth and the area to be restored are required in fixed Prosthodontics treatment for the laboratory to fabricate the desired restoration without any faults. The study aimed to raise awareness about the importance of improving individual skills to minimise impression errors, provide patients with high-quality prosthetics, and enhance their comfort. The study's objectives were to evaluate the clinically detectable errors in the impressions and to determine co-relations between possible risk factors that cause impression errors. This study follows a descriptive cross-sectional study design, which involves the probability convenience sampling technique, consisting of 150 impressions studied for the type of tray, type of material, type of technique, type of prosthesis ordered, arch of impression involved, size of tray, number of units prepared and retraction cord used. Impression errors were also assessed, including finish line errors, tears in the finish line, air bubbles, voids, and blood formed in the impression. Data were analysed with SPSS version 25.0, and correlations were found through a chi-square test. One hundred fifty impressions were analysed, with 80 being maxillary arch impressions. Most impressions utilised full arch trays (91.33%), with Monophase being the predominant technique (77%). Alginate emerged as the most commonly employed impression material (76%), and the most commonly used tray was the full arch tray (137). Crown preparations accounted for 70% of cases. Notably, retraction cord usage was observed in 58.7% of impressions. The study analysed 150 Impressions, finding 56.7% finish line errors, 21.3% tears, 19.3% bubbles, 80.7% voids, and 6% traces of blood. Our study reveals that material type, impression technique, no crown, arch of impression, prosthesis ordered, and retraction cord have a significant association (P < 0.05) with the impression errors, except tray type having no significant association (P > 0.05) with the impression errors. Based on the study's outcomes, this research identifies alginate and the monophase technique as prevalent choices among clinicians. The most common were voids and finish line errors, with tray selection showing no significant impact. The use of retraction cords notably reduces impression errors, indicating a strong association. Overall, crown impressions exhibit greater accuracy compared to bridge impressions.